Canadian Journal of Science, Mathematics and Technology Education - McDougall, Douglas; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer.)
The Canadian Journal of Science, Mathematics and Technology Education is the premier Canadian academic journal, and one of the leading journals internationally, in the field of STEM education. Published in both English and French, the journal aims to be both Canadian and international in scope. The journal provides a forum for the publication of original articles in a variety of styles, including research investigations using experimental, qualitative, ethnographic, historical, philosophical, or case study approaches; critical reviews of the literature; policy perspectives; and position papers, curriculum arguments, and discussion of issues in teacher education.
Keywords: Mathematics -- Study and teaching; Science education; Technical education; Science Education; Engineering/Technology Education; Mathematics Education